Sexual dimorphism of palatal dimensions among UPCD Students - Bagasan, Ana Dominique E.; Fayluga, Juvena B.; Magtanong, Danilo L. (Co-author).
Sex determination of a body is essential in criminal death investigations. While the pubic bone is considered by forensic investigators to have the best expressions of differences attributable to sex, it is often damaged in burials. On the other hand, palatal dimensions could provide another means for sex determination since the skull is said to have a high resistance to adverse environmental conditions. For this reason, the study aims to investigate the potential of palatal dimensions as a sex determinant. This cross sectional study was conducted at the University of the Philippines Manila and involved 65 of its 386 students enrolled in the second semester of the school year 2010-2011. The sampling population consists of 23 males and 42 females. Using the dental casts of the maxillary arch of each participant, the following were measured: (1) intercanine width, (2) line from the midpoint of the intercanine distance to a point in the crest of the incisive papilla, (3) palatal depth at the intercanine area, (4) interpremolar width, (5) midpoint of the interpremolar distance to a point in the crest of the incisive papilla and, (6) palatal depth at the interpremolar distance. The results were analyzed using the t-test with the p-value set at 0.05. It was observed that the mean values of the intercanine width, line from the midpoint of the intercanine distance to a point in the crest of the incisive papilla, interpremolar width, midpoint of the interpremolar distance to a point in the crest of the incisive papilla, and the palatal depth at both the intercanine and interpremolar areas were generally larger in males that in females. However, the values had no significant difference. The study shows that there is no significant difference between the palatal dimensions of male and female UPCD Students. Further studies about this topic is recommended.
Seminar Paper--Doctor of Dental Medicine--University of the Philippines Manila.